VII. REPLICATION, RESEARCH ACCUMULATION, AND META‐ANALYSIS IN DEVELOPMENTAL SCIENCE. Issue 2 (June 2017) - Card, Noel A.
Abstract : The progression of scientific knowledge requires replication of research results and an orderly accumulation of research knowledge. However, developmental science, like many other sciences, has too often prioritized individual studies at the expense of replication and synthesis efforts. In this chapter, I describe the concepts of replication and research accumulation and consider both their barriers and potentials for developmental science. I emphasize the importance of considering effect sizes rather than statistical significance, and I describe meta‐analysis as a powerful tool in facilitating research accumulation and in guiding replication efforts. By considering advancement in terms of research accumulation rather than single studies, developmental science can achieve greater efficiency and precision to guide both future research and applied efforts.